A case report on neurological Wilson disease in an adolescent boy - Paul, Sarmistha; Ratan, Piyush; Shankhwar, Rajat K.; Shankar, Udvaw; Anurag (International Journal of Research in Medical Sciences, 2024)
Wilson disease is an inherited metabolic multi-system disease that affects primarily the liver and brain. The cirrhotic liver combined with degenerative changes in lenticular nuclei of brain gives it the name of hepatolenticular degeneration. It is a rare disease involving the ATP7B gene and its protein. Here we discuss a case of a 15-year-old male who presented with predominantly neurological symptoms such as tremors, gait abnormality, dysphagia, and dysarthria which turned out to be a case of Wilson disease. Early identification is usually difficult since it has a long latent period and involves multiple systems with varied manifestations. It is a treatable with fair prognosis if diagnosed early.